PEMBERDAYAAN MASYARAKAT MELALUI DIVERSIFIKASI PRODUK LOKAL DI DESA EMPAT BALAI KECAMATAN KUOK - Mahyarni Mahyarni; Astuti Meflinda; Masrizal Masrizal; Dewi Diniaty (COMMUNITY SERVICE JOURNAL OF ECONOMICS EDUCATION, 2025)
Community empowerment is a process aimed at fostering awareness, willingness, and capability among community members to recognize their potential, as well as to preserve, protect, and improve their welfare independently. This research-based community service activity was conducted in Empat Balai Village, Kuok District, involving 20 participants who are micro, small, and medium enterprise (MSME) actors in the culinary sector. The method employed was Participatory Action Research (PAR), which emphasizes active community involvement in every stage of the program. The results show that the mentoring program for community empowerment through the diversification of food products based on local potential had a positive impact, as reflected in the high level of participation and enthusiasm among participants during the activity. Furthermore, the mentoring contributed significantly to improving the knowledge, skills, and insights of MSME actors in developing product innovations and expanding their business opportunities in the future.